2008
DOI: 10.1080/03640210802035084
|View full text |Cite
|
Sign up to set email alerts
|

Congruity Effects in Time and Space: Behavioral and ERP Measures

Abstract: Two experiments investigated whether motion metaphors for time affected the perception of spatial motion. Participants read sentences either about literal motion through space or metaphorical motion through time written from either the ego-moving or object-moving perspective. Each sentence was followed by a cartoon clip. Smiley-moving clips showed an iconic happy face moving toward a polygon, and shape-moving clips showed a polygon moving toward a happy face. In Experiment 1, using an explicit judgment task, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…We also included varying degrees of conceptual mapping in the experimental paradigm and our analysis revealed an amplitude difference that might arise from different degrees of mapping. Therefore, the results also offer evidence in support of the conceptual blending theory (Coulson & Van Petten, 2002;Fauconnier & Turner, 1998;Teuscher et al, 2008). The results support the theory by showing that literal and metaphorical sentences both involve mapping and that the mapping degree associates with the P600 amplitude.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We also included varying degrees of conceptual mapping in the experimental paradigm and our analysis revealed an amplitude difference that might arise from different degrees of mapping. Therefore, the results also offer evidence in support of the conceptual blending theory (Coulson & Van Petten, 2002;Fauconnier & Turner, 1998;Teuscher et al, 2008). The results support the theory by showing that literal and metaphorical sentences both involve mapping and that the mapping degree associates with the P600 amplitude.…”
Section: Discussionsupporting
confidence: 76%
“…The Conceptual Blending Theory (CBT) proposes that both literal and metaphoric expressions involve the construction of multiple cognitive models and establishment of mappings between the conceptual components in both target and source domains (Coulson & Van Petten, 2002;Fauconnier & Turner, 1998;Teuscher et al, 2008). For instance, in order to understand the sentence "That stone we saw in the natural history museum is a gem", a mapping must be established between a gem and the stone we saw in the natural history museum.…”
Section: Conceptual Blending Theory and Metaphor Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a presumption is by no means unusual since earlier cognitive studies have found that spatiotemporal reasoning is affected by conceptualizations of real, imagined, and fictive motion in physical and non-physical domains (Boroditsky & Ramscar, 2002;Matlock et al, 2005;Teuscher, McQuire, Collins & Coulson, 2008;see Ramscar, Matlock & Boroditsky, 2010 for a review).…”
Section: Motion As a Modulator Of Distance Expressionsmentioning
confidence: 98%
“…However, effects of temporal primes on spatial judgments have been found using a variety of paradigms and measures by Teuscher, McQuire, Collins, and Coulson (2008) and Ouellet, Santiago, Funes, and Lupiáñez (2010). The main problem of these cross-study comparisons to evaluate the degree of asymmetry of the effects is the diversity in tasks and measures.…”
mentioning
confidence: 99%